2017
DOI: 10.4103/0976-0105.195100
|View full text |Cite
|
Sign up to set email alerts
|

Utilization Study of Antihypertensives in a South Indian Tertiary Care Teaching Hospital and Adherence to Standard Treatment Guidelines

Abstract: Aim:Hypertension represents a major health problem primarily because of its role in contributing to the initiation and progression of major cardiovascular diseases. Concerns pertaining to hypertension and its sequelae can be substantially addressed and consequent burden of disease reduced by early detection and appropriate therapy of elevated blood pressure. This cross-sectional observational study aims at analyzing the utilization pattern of antihypertensives used for the treatment of hypertension at a tertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 25 publications
5
27
0
Order By: Relevance
“…The average number of CV drugs per prescription was 2.0, similar in both gender and close to previous reports on antihypertensive drugs in Nigeria 2.25 [16], 2 [30]. In contrast, a lower value was reported in South India at 1.78 [12]. The average number of diabetic drug per prescription was 1.7, also similar in both gender and consistent with the report of a previous study on anti-diabetic prescription in Southern Nigeria [20].…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…The average number of CV drugs per prescription was 2.0, similar in both gender and close to previous reports on antihypertensive drugs in Nigeria 2.25 [16], 2 [30]. In contrast, a lower value was reported in South India at 1.78 [12]. The average number of diabetic drug per prescription was 1.7, also similar in both gender and consistent with the report of a previous study on anti-diabetic prescription in Southern Nigeria [20].…”
Section: Discussionsupporting
confidence: 86%
“…There was a high prescription of CCB, particularly amlodipine in FCT district hospitals. This was reported in some other studies [11,12,39,40] while CCB has been reported as least prescribed [22,41]. Agents that act on the renin-angiotensin system hold a good share of the prescription, with Lisinopril and Telmisartan leading in the class similar to other studies [15,41].…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations